The Influence of KOMAT Media-Based Guided Inquiry Learning Model on Matrix Learning Outcomes of Vocational High School Students - Meila, Yuyun (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2024)
This study aims to (1) determine whether there is an influence of the KOMAT media-based Guided Inquiry learning model on the matrix learning outcomes of vocational high school students, and (2) determine the extent of the influence of the KOMAT media-based Guided Inquiry learning model on the matrix learning outcomes of vocational high school students. The study employs a quantitative approach and uses a quasi-experimental design with a posttest-only control group. The sampling technique used is purposive sampling. The research sample consists of class X TKRO 3 as the experimental group and class X TKRO 4 as the control group. Data were collected using test and documentation methods, while data analysis techniques included an independent sample t-test and effect size test. The results show that (1) the independent sample t-test on students' matrix learning outcomes yielded a Sig value of 0.000 < 0.05, thus H_1 was accepted, and (2) the effect size test results showed that the influence on students' matrix learning outcomes had an index of 1.932207, which, according to Cohen's table, corresponds to 97.1%, indicating a high category